Hubungan Postur Kerja dengan Keluhan Gangguan Otot Rangka Akibat Kerja (Gotrak) pada Pekerja Unit Quality Control (QC) PT.X Banten - Fierdania Yusvita; Hadi Nugroho (Universitas Malahayati Lampung, 2026)
ABSTRACT Work-Related Musculoskeletal Disorders are an ergonomic risk that can affect every worker, including workers in the Quality Control (QC) Unit. The work process in the QC Unit of PT.X involves a series of activities such as analyzing and testing raw materials, analyzing production processes up to the final product, and compiling reports. These activities are often not supported by an ergonomic working posture, thus increasing the incidence of musculoskeletal pain complaints. The aim of this study was to determine the relationship between work posture and GOTRAK complaints in QC Unit workers at PT.X. This study used a quantitative research method with a cross-sectional research design, conducted on 30 workers in the QC Unit of PT.X. Work posture assessment was performed using the Rapid Office Strain Assessment (ROSA), while WMSDs complaints were measured using the Nordic Body Map (NBM). Data analysis was conducted using the Chi-square test. 63.3% of workers had GOTRAK complaints with the highest complaints in the neck, back and waist. Statistical test results showed a p value = 0,028, so it was concluded that there was a relationship between work posture andGOTRAK complaints. Work posture has been proven to be related to GOTRAK complaints. It is recommended that PT.X increase its commitment to managing ergonomic hazards and risks by improving work design, providing education on ergonomic work processes, and ensuring that ergonomic risks in the form of GOTRAK complaints can be controlled in accordance with applicable regulations. Keyword: Work-Related Musculoskeletal Disorders, Work Posture, Ergonomics. ABSTRAK Gangguan Otot Akibat Pekerjaan (GOTRAK) merupakan risiko ergonomi yang dapat menimpa setiap pekerja, termasuk pekerja di Unit Quality Control (QC). Proses pekerjaan di Unit QC PT.X merupakan rangkaian aktivitas seperti menganalisis dan menguji bahan baku, menganalisis proses produksi sampai dengan produk serta menyusun laporan, hal ini seringkali tidak ditunjang oleh postur kerja ergonomis sehingga meningkatkan keluhan nyeri muskuloskeletal. Tujuan penelitian ini adalah mengetahui hubungan postur kerja dengan keluhan GOTRAK pada pekerja Unit QC PT.X. Penelitian ini menggunakan metode penelitian kuantitatif dengan desain penelitian cross sectional yang dilakukan pada 30 orang pekerja Unit QC PT.X. Penilaian postur kerja menggunakan Rapid Office Strain Assessment (ROSA), sedangkan keluhan GOTRAK diukur menggunakan Nordic Body Map (NBM). Analisis data menggunakan uji Chi-square. Sebanyak 63,3% pekerja memiliki keluhan GOTRAK dengan keluhan tertinggi pada bagian leher, punggung dan pinggang. Hasil uji statistik menunjukkan hasil p value = 0,028 sehingga disimpulkan terdapat hubungan antara postur kerja dengan keluhan GOTRAK. Postur kerja terbukti memiliki hubungan dengan keluhan GOTRAK. Disarankan kepada PT.X untuk meningkatkan komitmen pada pengelolaan bahaya dan risiko ergonomi berupa perbaikan desain kerja, edukasi terkait proses kerja yang ergonomis dan memastikan risiko ergonomi berupa keluhan GOTRAK dapat dikendalikan sesuai peraturan yang berlaku. Kata Kunci: GOTRAK, Postur Kerja, Ergonomi.